Hubungan Kualitas Tidur dengan Nyeri Kepala Primer pada Masyarakat Daerah Pesisir Desa Nusalaut, Ambon - PRISKILLA ROSSE GRATIA HABEL; PARNINGOTAN YOSI SILALAHI; YUNIASIH TAIHUTTU (Smart Medical Journal, 2018)
Introduction: Sleep disorders and primary headaches (NKP) is a common disease in the community and both relate reciprocally. Some of the factors associated with  the  onset  of  primary headache include poor sleep quality, fatigue, change in temperature. Coastal communities are groups of people who have high risk factors for developing such disorders. This study aimed to explore the relationship between quality of sleep and primary headaches in coastal communities in Nusalaut  which never held backward.Methods: Data was collected by using a cross sectional study conducted in communities in Nusalaut amounted to 190 people with data retrieval techniques cluster random sampling. Quality of sleep was assessed by The Pitssburg Sleep Quality Index (PSQI), while primary headache was assessed by questionnaire and Ong BK KH HO-C. Descriptive analysis to determine the characteristics of the subject while the correlation between sleep quality with primary headache is done by Spearman correlation test.Results: The results showed there is a significant association between factors such as gender, age and type of work with quality bedding and primary headaches while between quality of sleep and primary headaches do not have a meaningful correlation with the strength of the correlation was very weak (p = 0.323).  Conclusion: there was no significant correlation between quality of sleep and primary headaches.